2017
DOI: 10.1259/dmfr.20160296
|View full text |Cite
|
Sign up to set email alerts
|

Imaging evaluating of the implant/bone interface—an in vitro radiographic study

Abstract: Conventional radiographs or digital radiographs with high-pass filters could help enhance diagnosis on implant-bone interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 17 publications
0
6
0
1
Order By: Relevance
“… 8 The extent of periodontitis is measured to indicate the treatment and monitor the treatment response. Bone loss can be measured on radiographs, 9 and mobility is measured via manual manipulation. 10 The degree of inflammation is subjective and is based on the color of the gingiva and the frequency of bleeding on probing.…”
Section: Introductionmentioning
confidence: 99%
“… 8 The extent of periodontitis is measured to indicate the treatment and monitor the treatment response. Bone loss can be measured on radiographs, 9 and mobility is measured via manual manipulation. 10 The degree of inflammation is subjective and is based on the color of the gingiva and the frequency of bleeding on probing.…”
Section: Introductionmentioning
confidence: 99%
“…The studies used PR, PAN, MRI, CT, and CBCT, in Ti 12 13 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 and ZrO 2 12 13 23 36 43 implants. The descriptive characteristics of the studies are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The use of filters is a post-processing image manipulation that has yielded positive results in improving diagnostic performance in both Ti and ZrO 2 implants. 25 39 For ZrO 2 , Bayrak et al 23 found that the adaptive image noise optimiser filter with MAR improved interobserver agreement in the detection of bone defects. Another aspect that positively influenced diagnostic performance was the size of bone defects.…”
Section: Discussionmentioning
confidence: 99%
“…Choi JW et al (2011) confirmed that for a 3D x-ray, the use of CBCT (cone beam computed tomography-diagnostic aid used when the conventional x-rays fail as a diagnostic tool (Shah et al 2014)) should be preferred over a CT (computed tomography) image but it has a high radiation dose. According to Michele M Vidor et al (2017), radiographic image of the boneimplant interface is influenced by two factors, the radiographic system, and the processing filter employed. The results from this study are that conventional radiographs or digital images with application of high-pass filters such as "Caries2" and "Endo" could help enhance diagnosis on the implant-bone interface on intraoral radiographs so it could help too in the identification of different implant systems and hence aid in the identification of different implant systems.…”
Section: Aesthetic Biological Restoration Mechanical and Occlusion mentioning
confidence: 99%